Expressive Speech Acts and Strategic Communication in Prabowo Subianto's 2024 Presidential Campaign Speeches - Shahrizan Mangku Bumi; Silvia Marni; Refa Lina Tiawati (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This study explores the use of expressive speech acts and their associated strategies in Prabowo Subianto's speeches during the 2024 presidential election campaign. By analyzing video content from YouTube channels such as KOMPASTV, Bisnis.com, Warta Kota Production, and Liputan6, the research identifies the forms and strategies of expressive speech acts employed. Utilizing a qualitative descriptive methodology, the study follows a four-stage process: transcription, classification, analysis, and conclusion. Findings reveal seven forms of expressive speech acts: thanking, complaining, congratulating, flattering, praising, blaming, and criticizing. These forms reflect nuanced aspects of interpersonal and political communication. The strategies identified include straightforward approaches without pleasantries, those incorporating positive politeness, strategies with negative politeness, and shared speech approaches. The research highlights the role of expressive speech acts in shaping political narratives and fostering connections with the electorate during campaign discourse. This study contributes to the understanding of pragmatic strategies in political communication and their influence on public engagement